Pengaruh Kebijakan Pemekaran Wilayah Kecamatan Terhadap PelayananPublik (Suatu Studi di Kecamatan Kema Kabupaten Minahasa Utara) - Wumu, Harianto Ardiansyah; Lengkong, Florence Daicy; Dengo, Salmin (Sam Ratulangi University, 2015)
Abstract : The establishment of autonomous regions is intended to optimize the governance intended tocreate regional governments are better able to optimize public services and improve local communityempowerment on a wider scale luas.Namun there are obstacles and complaints that occur inorganizing services to the community such as, yet effective, efficient , transparent, responsive, fair andresponsible. This study aimed to determine and quantify the effect of the sub-district division policy onpublic services in the district of North Minahasa regency Kema. The method used in this study using aquantitative correlation with the approach of quantitative analysis using statistical formulas descriptiveand inferential statistics. The results were obtained the following equation: Y = 6.534 + 0.956 X. Theregression coefficient b = 0.956 which is positive, clearly demonstrates that the functional relationship/ influence kebijakanpemekaran variable regions with public services is positively associated with thedevelopment pattern of 1: 0.956; means change / improvement of division policy wilayahsebesar 1scale / unit will cause a change / improvement of public services 0.837 units / scale. Pattern functionalrelationship / influence of division policy on public services is very significant or very significant, asdemonstrated by the results of testing the significance of regression with F-test obtained value of F =298,212pada significant level of 0.000 y = 6.534 + 0.956 (60) = 63.894The prediction accuracy of the calculation results above indicate that if the quality of division policycould be improved by the value (score) ideal variables (ie 60) of the present condition, it candiprediksiakan an increase in public services in the district amounted to 63.894 scale Kema. Thisprediction calculation results may indicate that the expansion policy of the districts peningkata asignificant effect on public services;Keywords: influence, regional divisions, to service publk